Ullmann's chemical engineering and plant design. - Ullmann, Fritz, 1875-1939 (Wiley-VCH, 2005)
Annotation Ullmann's Chemical Engineering and Plant Design is the one-stop resource for the plant design engineering community Since the unabridged 40-volume Ullmann's Encyclopedia is inaccessible to many readers - particularly individuals, smaller companies or institutes - all the information on chemical engineering and plant design has been condensed into this convenient two-volume set. Starting with the quantitative treatment and fundamentals of chemical engineering, it combines all aspects of process development and reactor technology, as well as detailing their practical applications in sections devoted to plant design, scale-up and plant safety. The two volumes are rounded off by a keyword and an author index. Throughout, readers benefit from the rigorous and cross-indexed nature of the parent reference, and will find both broad introductory information as well as in-depth details of significance to industrial and academic environments.
Keywords: Chemical engineering.; Chemical plants -- Design and construction.; Chemical engineering -- Planning.; elektronické knihy; electronic books